2021
DOI: 10.1038/s41419-021-03542-w
|View full text |Cite
|
Sign up to set email alerts
|

Exovesicular-Shh confers Imatinib resistance by upregulating Bcl2 expression in chronic myeloid leukemia with variant chromosomes

Abstract: Chronic myeloid leukemia (CML) patients with complex chromosomal translocations as well as non-compliant CML patients often demonstrate short-lived responses and poor outcomes on the current therapeutic regimes using Imatinib and its variants. It has been derived so far that leukemic stem cells (LSCs) are responsible for Imatinib resistance and CML progression. Sonic hedgehog (Shh) signaling has been implicated in proliferation of this Imatinib-resistant CD34(+) LSCs. Our work here identifies the molecular mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…It is the rate-limiting enzyme in sucrose synthesis and affects sucrose accumulation in plants ( Wang et al, 2017b ). It is reported that overexpression of a maize SPS gene in potatoes enhanced the rate of photosynthesis and increased yield ( Ishimaru et al, 2008 ). Therefore, the low level of SPS protein in pH 5 may inhibit plant growth by affecting carbon metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It is the rate-limiting enzyme in sucrose synthesis and affects sucrose accumulation in plants ( Wang et al, 2017b ). It is reported that overexpression of a maize SPS gene in potatoes enhanced the rate of photosynthesis and increased yield ( Ishimaru et al, 2008 ). Therefore, the low level of SPS protein in pH 5 may inhibit plant growth by affecting carbon metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The application of high N fertilizer increases the levels of accumulation of total, α-, γ-, and ω-gliadins in bread wheat ( Chope et al, 2014 ; Zhen et al, 2020 ). So, N application strategies are one of the most common management practices to regulate yields and protein content in wheat ( Nakano and Morita, 2009 ; Yu et al, 2018 ). The two RNAi lines used in this work differ in the endosperm-specific promoters used for silencing; a D-hordein promoter ( Pistón et al, 2008 ) in the case of line D783, and a γ-gliadin promoter ( Pistón et al, 2009 ) in line D793.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these RNAi varieties showed decreases of up to 100-fold in the ability to stimulate the immune response of T cells that specifically recognize α-gliadins epitopes ( Gil-Humanes et al, 2010 ) and an impaired capacity to stimulate Peripheral Blood Mononuclear Cells (PBMCs) from CD patients, providing a stimulatory response that does not differ from the gluten-free negative control ( Sánchez-León et al, 2019 ). In addition, N fertilization is a common practice to regulate yields and protein content in wheat ( Nakano and Morita, 2009 ; Yu et al, 2018 ), and an increase in N fertilization rates promotes the increment of total gluten content, including all gliadin fractions. These RNAi varieties also showed markedly different responses in relation to N fertilization, related to the RNAi construct used for gliadin silencing, increasing the gliadin content when nitrogen is increased ( García-Molina and Barro, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In soybeans, short-term and moderate water deficit during the vegetative stage may not reflect drastic reductions in grain yield since this period can be compensated by rainfall during the reproductive stage. However, in the reproductive period and, mainly during pod filling stage, drought can result in severe productivity losses ( Oya et al, 2004 ; Xu et al, 2018 ). Therefore, six progeny plants of the lines 4-3 and 4-23, together with the WT control, were subjected to water stress at the R2 stage, when open flowers are observed at the uppermost nodes of the main stem ( Fehr and Caviness, 1977 ).…”
Section: Resultsmentioning
confidence: 99%